2022
DOI: 10.1111/jocn.16460
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ perceptions and experiences of support to be a parenting partner during the perinatal period: A scoping review

Abstract: Aims and objectives The aim of this study was to explore fathers’ perceptions and experiences of support in the perinatal period. Change in society has seen the increased visibility of fathers being involved during pregnancy and engaging in their infants’ lives and the expectation and benefits of men playing an equal and direct role in caring for their children. However, less is known about the nature of support that fathers require to facilitate this role transition. Design A scoping review was conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 76 publications
(250 reference statements)
0
8
0
Order By: Relevance
“…We know from to the literature that paternal mental ill-health can lead to adverse child outcomes by a combination of pathways, modified by child characteristics and parental psychosocial factors [ 64 ]. Fathers tend to seek support related to parenting and mental health among their social network or they may seek informational support online [ 65 , 66 ]. Some turn to their GP when mental health problems become severe [ 65 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know from to the literature that paternal mental ill-health can lead to adverse child outcomes by a combination of pathways, modified by child characteristics and parental psychosocial factors [ 64 ]. Fathers tend to seek support related to parenting and mental health among their social network or they may seek informational support online [ 65 , 66 ]. Some turn to their GP when mental health problems become severe [ 65 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some turn to their GP when mental health problems become severe [ 65 , 67 ]. Formal support from paternal groups is rarely accessible but may be desired by fathers [ 65 , 66 , 68 ]. Some fathers have previously emphasised the importance of addressing and normalising psychosocial challenges related to becoming a father [ 67 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers said that accessing the program from their own home meant that their partner was also able to participate—and this meant that both partners could learn to implement the strategies and experience increases in parenting confidence. There is now a wide body of evidence pointing to the important role that fathers or secondary caregivers can have in early parenting, and the positive impacts that this can have on the father–child relationship (Shorey & Ang, 2019) and the partner relationship (Leahy‐Warren et al., 2023). Research has also found that father involvement can predict lower levels of maternal depression (Maselko et al., 2019) and buffer the effects of maternal depression on child outcomes (Cimino et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…When fathers strive to be acknowledged as part of the caring team, their opportunity to be an important source of information and to be a mutual partner in caring for their child is not being looked after. The feeling of not being acknowledged does not seem to be a unique experience for fathers of children with C3 conditions but is a shared experience by fathers in general (Chin et al, 2011; Høgmo et al, 2021; Leahy‐Warren et al, 2022). This might indicate a structural problem in fathers' role within paediatric health care.…”
Section: Discussionmentioning
confidence: 99%